Analysis of Cost Sharing on the Satisfaction of NHI Patients Not Contribution Beneficiaries (Case Study of Passo Hative Hospital in Ambon City) (Medico Legal Update, 2020)
Cost Sharing is a fee payable by the patient participant of the social insurance administration Organizationbecause it gets health services in the hospital which is derived from the reduction in tariffs with the amountof costs incurred by the social insurance administration Organization. Analyse the additional costs that thePasso Hative Hospital has done to patient satisfaction. This type of research is quantitative research by usinga cross-sectional design approach. The population in this study is all the patients of the national health careinsurance not the recipient of dues \who are being treated at hospitalisation in the Passo Hative Hospitalin Ambon City with the last one month visit was 150 patients. The sampling techniques in this study areaccidental sampling. The results showed there was an additional cost relationship moving the treatmentclass to patient satisfaction (P = 0.001). There is a relationship of medical services additional costs to patientsatisfaction (P = 0,016) and there is a connection to the additional cost of medication to patient satisfaction(P = 0,000) of the hospital as a service provider of the social insurance administration Organization in orderto be more observant to see the cause of the users of the social insurance administration Organization tochange the treatment class of the care and fulfill and complement medical services and medicines that arethe right of the patient according to the social insurance administration Organization.